Discussion of LIFO and the Diffusion of Innovation - Nash, Manning (Journal of Accounting Research, 1971)
As an anthropologist when I first decoded the acronym LIFO I thought it was an accountant's discovery of the American cultural norm for hiring and firing ethnic minorities. Later I discovered that LIFO is a form of inventory accounting which, under the proper conditions, can have significant effects on tax assessments. Apparently LIFO is a later invention than the apparently more widespread and natural mode of inventory accounting, FIFO. Although the authors do not so state, LIFO and FIFO do not exhaust between them the possible accounting procedures for reckoning inventory. Copeland and Shank proposed to treat LIFO as an innovation and to trace its through the sampled world of firms. To study the spread of an innovation, the behavioral sciences have developed several variants of a diffusion model. An accountant must choose among the models, make them applicable to his empirical universe, and draw legitimate and testable inferences from that exercise. The models chosen by the authors are placed in a binary set: positive for the Rogers model and negative for the Griliches cost-benefit model. They use the Rogers model (somewhat modified) to show that its explanatory power for the spread of LIFO is greater than the economist's single variable model. The Rogers model is a social-psychological one and suited to aggregate data as that is generated via questionnaire, census or interview. But in contemporary sociology and anthropology the Rogers model is only partial and needs supplementing by variables that pay attention to more than the mental process between the perception of relative advantage and the adoption of an innovation. The Rogers model lacks important specific elements in the understanding of diffusion. Specifically, it lacks the sociological variables of channels